2021
DOI: 10.21142/2523-2754-0903-2021-078
|View full text |Cite
|
Sign up to set email alerts
|

Educación virtual en odontología durante la pandemia de COVID-19

Abstract: Los cambios en la educación universitaria que surgieron en el contexto de la pandemia de COVID-19 supusieron nuevos retos en todo el mundo. En el caso de la educación odontológica, si bien ya se había intentado la implementación de recursos virtuales, un enfoque completamente virtual fue un nuevo desafío. El objetivo de este artículo es discutir sobre la educación virtual en el área odontológica en el contexto de la pandemia de COVID-19 y los retos que representa. Se concluyó que, para lograr la continuación d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
0
1
1
Order By: Relevance
“…The present study was conducted two years after the beginning of the pandemic (year 2022) and possibly with the passage of time the conditions and the educational environment improved, providing better learning. 39 The results obtained are not similar to those reported by Herr et al 34 who found that 74.1% of students showed good satisfaction. This may be explained by the fact that this study was conducted only in third year dental students.…”
Section: Discussioncontrasting
confidence: 69%
“…The present study was conducted two years after the beginning of the pandemic (year 2022) and possibly with the passage of time the conditions and the educational environment improved, providing better learning. 39 The results obtained are not similar to those reported by Herr et al 34 who found that 74.1% of students showed good satisfaction. This may be explained by the fact that this study was conducted only in third year dental students.…”
Section: Discussioncontrasting
confidence: 69%
“…De la misma manera, en varios países desde mucho antes de la pandemia ya se había integrado las TIC como complemento en la enseñanza, obteniendo una buena aceptación por parte de los estudiantes 5,7 . Y en los últimos años, a partir de la pandemia provocó un incremento de los recursos digitales en las distintas áreas de odontología, desde la inclusión de las redes sociales, videoconferencias, canales educativos, y programas educativos en 3D 8 .…”
Section: Antecedentes De La Virtualidad En Odontologíaunclassified